Protective Effect of Ursolic Acid on the Intestinal Mucosal Barrier in a Rat Model of Liver Fibrosis - Zhang, Wang; Gan, Dakai; Jian, Jie; Huang, Chenkai; Luo, Fangyun; Wan, Sizhe; Jiang, Meichun; Wan, Yipeng; Wang, Anjiang; Li, Bimin; Zhu, Xuan (Frontiers in Physiology, 2019)
Oxidative stress mediated by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) plays an important role in intestinal mucosal barrier damage in various disease states. Recent evidence suggests that intestinal mucosal barrier damage and intestinal dysbiosis occur in mice with hepatic fibrosis induced by CCl4 or bile duct ligation. Another study showed that ursolic acid (UA) attenuates experimental colitis via its antiinflammatory and antioxidant activities. The goal of this study was to investigate the effects of UA on the intestinal mucosal barrier in CCl4-induced hepatic fibrosis rats and identify its associated mechanisms. Male Sprague-Dawley (SD) rats were randomly divided into the following 3 groups (n=10/group): the control, CCl4 model and UA treatment groups. Rats were sacrificed at 72 h after the hepatic fibrosis model was established and assessed for liver fibrosis, intestinal injury, enterocyte apoptosis, bacterial translocation, system inflammation, intestinal oxidative stress, and tight junction protein and NOX protein expression. The results demonstrated that UA attenuated the following: ⅰ) liver and intestinal pathological injury; ⅱ) cleaved caspase-3 expression in the ileal epithelial cells; ⅲ) serum lipopolysaccharide and procalcitonin levels; ⅳ) intestinal malondialdehyde levels; and ⅴ) the expression of the NOX protein components NOX2 and P67phox in ileal tissues. Furthermore, our results suggested that UA improved intestinal dysbiosis and the expression of the tight junction proteins Claudin 1 and Occludin in the ilea of rats. These results indicate that UA has protective effects on the intestinal mucosal barrier in rats with CCl4-induced liver fibrosis by inhibiting intestinal NOX-mediated oxidative stress. Our findings may provide a basis for further clinical studies of UA as a novel and adjuvant treatment to cure liver fibrosis.